The Influence of The Power Of Two Type Of Cooperative Learning Model On The Learning Achiement Of Cililitan IV SDN Grade Students On Magnetic Material - Rani; Budi Hendrawan; M. Fahmi Nugraha (Jurnal Sekolah Dasar, 2020)
Natural science is one of the subjects contained in the elementary or elementary level curriculum. In line with the learning of natural science in elementary school, learning natural science is one of the subjects that is still considered difficult by. In science learning there are several obstacles, namely the low student learning achievement, in the learning process in the classroom still using conventional learning models only with lectures and centered on textbooks only, there is no group discussion students tend to be passive and the teacher becomes the center of the learning process, so that students in science learning in the classroom feels boring and less challenging so students are less active in class. Based on the problem of difficulties in the learning process, the application of the power of cooperative tipe the power of two expected to be able to improve student learning achievement on magnetic material of class IV SDN Cililitan. The study uses quantitative research methods with experimental research methods using quasi-external design with nonequivalent control group design. The study was conducted at SDN Cililitan with a population of eighteen students by using a saturated sample that divides students into two classes, namely the control class of ten students and the experimental class of ten students. Data collection techniques were performed using pretest and posttest tests and the data were analyzed using SPSS version 16.